) If the worshiper doubts between two and three, or between three and four, then builds on the most, is it enough to be on the safe side with a standing rak’ah, or is it necessary to do two rak’ahs [sitting]? Study and investigation) (Journal of the College of Basic Education, 2023)
This research came to study one of the symbols of the Akhbari school in the twelfth century AH, as it dealt with one of his jurisprudential writings. After relying on God and choosing research to be the subject of my thesis to obtain a master’s degree, I reviewed the catalogs of libraries that contain these valuables. So my share of the investigation was thirty-five issues, to participate in the revival of the Islamic heritage for the benefit of the people in general and the request for knowledge in particular, and here Iwill address the investigation of one of the issues of the manuscript.